Awareness and Utilisation of Artificial Intelligence as a Pedagogical Tool and Catalyst for Enhancing Pre-Service Teachers’ Quality - Popoola, Abiola Babatunde; Obilo, Princess Ijeoma; Ademola, Olaitan Idowu (Kashere Journal of Education, 2025)
The paradigm in education is shifting from a knowledge-oriented curriculum to one focused on skills and critical thinking. Additionally, the preparation of teachers is shifting from a knowledge-based to a pedagogically orientated curriculum to enhance classroom interactions and support learners’ learning. This paper, therefore, is set out to critically discuss the emergence of AI tools as a pedagogical innovation for teaching, as well as an important pedagogical tool to support the preparation of quality pre-service in the nation’s teacher preparation schools. The paper began with a discussion of general education and the specialised field of teacher education. It further discussed what AI is, the importance of AI in the educational process and why teacher education should adopt AI pedagogy in the preparation of pre-service teachers to enhance their quality. The paper, however, recommended that awareness capacity-building workshops be organised for teacher educators and for pre-service teachers on how to responsibly use and adopt AI tools to enhance and support their learning. The government should also make provisions to ensure constant and stable electricity to support the use of digital technologies that enable the adoption of AI as a pedagogical tool, among others.